Pembangunan Desa Wisata Senaru dalam Konsep Public Private Partnership - Septiadi, Septiadi Septiadi; Rahmi, Siti Atika; Jailani, Muhammad Aprian (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
This study aims to provide knowledge about how partnerships are carried out between the government and the private sector in the Development of Senaru Tourism Village. This research uses a descriptive approach with a qualitative approach method. Data collection techniques by conducting interviews by preparing several questions to informants, namely the Senaru Village government and private parties. Second, observation by making direct observations by researchers in Senaru Tourism Village. Third, Documentation with shooting in the field. The development of Senaru Tourism Village uses the concept of partnership where cooperation between the government and the private sector uses the approach of "Building, Operating and Transfer". Senaru Village Government has several assets or work units in the field of tourism. Among them there are Waterfall Attractions, Speda Tourism, Cultural Tourism, Traditional House Tourism, Ripertabing Tourism, and other tourist facilities, then the Private Sector plays a role in field operations both in the process of tourist activities and in the development process. Then the second approach is "Build, Own and Operate". Private parties own assets such as villas, hotels, inns and other facilities that are managed privately without any interference from the government.